2015
DOI: 10.3233/jpd-150632
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Surgery and Post-Operative Cognitive Decline in Idiopathic Parkinson’s Disease: Considerations from a Pilot Study

Abstract: BACKGROUND Post-operative cognitive dysfunction (POCD) demarks cognitive decline after major surgery but has been studied to date in “healthy” adults. Although individuals with neurodegenerative disorders such as Parkinson’s disease (PD) commonly undergo elective surgery, these individuals have yet to be prospectively followed despite hypotheses of increased POCD risk. OBJECTIVE To conduct a pilot study examining cognitive change pre-post elective orthopedic surgery for PD relative to surgery and non-surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…There was no evidence of DVT, embolism, or nerve palsy. Two of our patients suffered from transient delirium and were controlled with olanzapine, which confirmed that orthopedic surgery could induce a cognitive decline in PD patients [20]. Recently, some database studies [2126] showed both TKA and THA in PD patients provide a higher complication rate, longer LOS, and higher charges than the controlled cohort.…”
Section: Discussionsupporting
confidence: 66%
“…There was no evidence of DVT, embolism, or nerve palsy. Two of our patients suffered from transient delirium and were controlled with olanzapine, which confirmed that orthopedic surgery could induce a cognitive decline in PD patients [20]. Recently, some database studies [2126] showed both TKA and THA in PD patients provide a higher complication rate, longer LOS, and higher charges than the controlled cohort.…”
Section: Discussionsupporting
confidence: 66%
“…6,7 This change better aligns these disorders with the phenotypically similar neurocognitive diagnoses listed in the Diagnostic and Statistical Manual of Mental Disorders, version 5, such as Alzheimer disease [8][9][10][11][12][13][14] and Parkinson disease. 15 Clinical studies have identified age, infection, and preexisting cognitive disorders as consistent risk factors for perioperative neurocognitive disorder 6 ; perioperative features, such as surgery duration, anesthetic management, and intraoperative physiology (e.g., hypotension, hypoxemia) have not been rigorously implicated. In fact, other than the most acute forms of dysfunction (e.g., postoperative delirium), the relationship of postoperative cognitive impairment with the surgery or anesthetic itself remains uncertain.…”
mentioning
confidence: 99%
“…Most of the studies indicate an increase in severity of the disease post operatively on a long-term basis [ 7 , 8 ]. This change can be detected by worsening cognition, impaired righting reflexes or an increase in muscle imbalance [ 16 ].…”
Section: Factors Affecting the Outcome For Total Knee Arthroplasty Inmentioning
confidence: 99%